Exploring medical leader identity and its formation. Issue 4 (20th September 2019) - Maile, Emily; McKimm, Judy; Till, Alex
Abstract : Purpose: "Becoming" a doctor involves the acquisition of medical knowledge, skills and professional identity. Medical professional identity formation (MPIF) is complex, multi-factorial and closely linked to societal expectations, personal and social identity. Increasingly, doctors are required to engage in leadership/management involving significant identity shift. This paper aims to explore medical professional identity (MPI) and MPIF in relation to doctors as leaders. Selected identity theories are used to enrich the understanding of challenges facing doctors in leadership situations and two concepts are introduced: medical leader identity (MLI) and medical leader identity formation (MLIF) and consideration given to how they can be nurtured within medical practice. Design/methodology/approach: A rapid conceptual review of relevant literature was carried out to identify a set of relevant concepts and theories that could be used to develop a new conceptual framework for MLI and MLIF. Findings: MLIF is crucial for doctors to develop as medical leaders, and, like MPIF, the process begins before medical school with both identities influenced, shaped and challenged throughout doctors' careers. Individuals require support in developing awareness that their identities are multiple, nested, interconnected and change over time. Originality/value: This paper draws on concepts from wider literature on professional identity, in relation to how doctors might develop their MLI alongside their MPI. It offers a new perspective on MPI in the light of calls on doctors to "become and be healthcare leaders" and introduces the new concepts of MLI and MLIF.